A Qualitative Exploration of Students’ Perception on English Day Program at SMAN 1 West Sumatera - Munir, Sirajul; Zulhermindra, Zulhermindra; Putra, Hendra Eka; Fajriati, Fajriati (Jurnal Simki Pedagogia, 2023)
This present research is motivated by the English day program applied at SMAN 1 West Sumatera. This research aims to find out how students perceive the English day program at SMAN 1 West Sumatra. This research used a qualitative method. The research informants were students of the tenth grade of SMAN 1 West Sumatra who took part in English day in the 2021/2022 academic year who were selected by purposive sampling technique. In this research, the researchers acts as the key instrument. Data collection techniques was interviews. Data collection tools were obtained from interview guides, recorders, and field notes. To test the validity of the data, the researchers conducted time triangulation. Data analysis was carried out in three stages: data reduction, data presentation, and conclusion drawing and verification. The results of the data analysis show several students’ perception on English day program at SMAN 1 West Sumatera. The perceptions include: (1) enriching students’ vocabulary; (2) improving students’ grammar mastery; (3) enhancing students’ speaking skills; (4) improving students’ pronunciation; and (5) increasing students’ understanding of English. The negative perception, however, is English day program burdens the students with the punishment. These findings recommend English day program remain to conduct at SMAN 1 West Sumatera.